RET fusion genes in pediatric and adult thyroid carcinomas: cohort characteristics and prognosis - Bulanova Pekova, Barbora; Sykorova, Vlasta; Mastnikova, Karolina; Vaclavikova, Eliska; Moravcova, Jitka; Vlcek, Petr; Lancova, Lucie; Lastuvka, Petr; Katra, Rami; Bavor, Petr; Kodetova, Daniela; Chovanec, Martin; et al. (Endocrine-related cancer, 2023)
Thyroid cancer is associated with a broad range of different mutations, including RET (rearranged during transfection) fusion genes. The importance of characterizing RET fusion-positive tumors has recently increased due to the possibility of targeted treatment. The aim of this study was to identify RET fusion-positive thyroid tumors, correlate them with clinicopathological features, compare them with other mutated carcinomas, and evaluate long-term follow-up of patients. The cohort consisted of 1564 different thyroid tissue samples (including 1164 thyroid carcinoma samples) from pediatric and adult patients. Samples were analyzed for known driver mutations occurring in thyroid cancer. Negative samples were subjected to extensive RET fusion gene analyses using next-generation sequencing and real-time PCR. RET fusion genes were not detected in any low-risk neoplasm or benign thyroid tissue and were detected only in papillary thyroid carcinomas (PTCs), in 113/993 (11.4%) patients, three times more frequently in pediatric and adolescent patients (29.8%) than in adult patients (8.7%). A total of 20 types of RET fusions were identified. RET fusion-positive carcinomas were associated with aggressive tumor behavior, including high rates of lymph node (75.2%) and distant metastases (18.6%), significantly higher than in NTRK fusion, BRAF V600E and RAS-positive carcinomas. Local and distant metastases were also frequently found in patients with microcarcinomas positive for the RET fusions. 'True recurrences' occurred rarely (2.4%) and only in adult patients. The 2-, 5-, 10-year disease-specific survival rates were 99%, 96%, and 95%, respectively. RET fusion-positive carcinomas were associated with high invasiveness and metastatic activity, but probably due to intensive treatment with low patient mortality.
Keywords: nádory štítné žlázy; mutace; Proto-Oncogene Proteins c-ret; dospělí; dítě; protoonkogenní proteiny B-raf; Adult; Adolescent; Thyroid Cancer, Papillary; lidé; Mutation; Carcinoma; karcinom; prognóza; protoonkogenní proteiny c-ret; papilární karcinom štítné žlázy; Proto-Oncogene Proteins B-raf; Thyroid Neoplasms; Prognosis; Child; mladiství; Humans